A Dual-Band Implantable Antenna for Mobile Systems - Qasim Kamil, Ansam (Engineering, Technology & Applied Science Research, 2025)
In this paper, a miniaturized dual-band implantable antenna is presented for mobile communication services, as well as industrial and scientific applications. The proposed antenna, with compact dimensions of 37 × 35 × 1.6 mm³, operates efficiently at dual frequencies of 3.7 GHz and 6.2 GHz. It features a circular metal patch with rectangular-shaped slots, enabling stable radiation patterns, broadband impedance matching, and robust performance. The antenna achieves a gain of 3.47 dBi, a directivity of 4.5, and an efficiency of 86%, making it well-suited for 5G technology and other high-frequency applications. Compared to existing designs, the proposed antenna demonstrates significant improvements in efficiency and bandwidth while maintaining a compact size. These antennas are essential for handling the increased data demands and diverse frequency requirements of modern mobile systems. Future trends in wireless communication are rapidly evolving, addressing challenges, such as interference reduction, increased data demands, and enhanced network performance. The proposed antenna, with its high efficiency and compact design, aligns with these trends and is well-positioned to meet the requirements of the next-generation communication systems.